The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand - Seldon F.l.s., David S.; Buckley, Thomas R. (Zootaxa, 2019)
Mecodema (Coleoptera: Carabidae: Broscini) is a hyperdiverse endemic New Zealand genus of ground beetles with only a few geographically widespread species found throughout the two main islands, as well as many offshore islands. Using specimens from a number of private and institutional collections, in addition new specimens were acquired by extensive pitfall trapping, we describe or redescribe all of the known North Island Mecodema species. Additionally, we redescribe three South Island species from the former genus Metaglymma, as morphological evidence shows that these species are nested within Mecodema. Species descriptions are formed by using 128 morphological characters, which include external characters, as well as both male and female internal structures. There are four new combinations: Mecodema antarctica comb. n., M. aberrans comb. n., M. moniliferum comb. n. and M. tibiale comb. n. We synonymise M. occiputale under Mecodema curvidens, and M. sulcatum under Mecodema oblongum, and reinstate M. scitulum Broun (northwest Hunua Range, Auckland). Twenty four new species are described: Mecodema argentum sp. n., M. atuanui sp. n., M. dunnorum sp. n., M. genesispotini sp. n., M. godzilla sp. n., M. jacinda sp. n., M. kipjac sp. n., M. kokoroiho sp. n., M. mohi sp. n., M. ngaiatonga sp. n., M. ngaitahuhu sp. n., M. papake sp. n., M. perexiguus sp. n., M. rusticulus sp. n., M. temata sp. n., M. teparawhau sp. n., M. teroroa sp. n., M. tewhara sp. n., M. tuhoe sp. n., M. undecimus sp. n., M. wharekahika sp. n., M. xylanthrax sp. n., M. yconomus sp. n., M. zonula sp. n. North Island regional species endemism is very high in Northland (15/16 endemic species), with species becoming more widespread in the southern regions, e.g. Wellington only has two endemic species from a total of eight species. This research increases the total number of described Mecodema species to 102, and will allow a modern taxonomic framework for completion of the revision of the South Island species.